Diet in two syntopic neotropical lizard species of Liolaemus (Liolaemidae): interspecific and intersexual differences - Halloy, Monique (2006)
The study of the diet of a species can help us understand its natural history and strategies involved in searching for food. Here we describe the diets of two syntopic lizard species from northwestern Argentina, Liolaemus quilmes and L. ramirezae. We compare the two species with respect to their general diet and we compare males and females of L. quilmes with respect to their favorite prey item, ants. Both species are insectivorous and diurnal, and they are of similar sizes, L. quilmes being slightly larger than L. ramirezae. We examined fecal samples of field captured lizards and stomach contents of preserved specimens from the Fundación Miguel Lillo (54 L. quilmes and 16 L. ramirezae). Prey items were identified to order and, in Formicidae (Hymenoptera), to species. The two Liolaemus species ate prey that belonged mainly to three insect orders: Coleoptera, Hemiptera (Heteroptera), and Hymenoptera. Liolaemus quilmes ate significantly more Hymenoptera than L. ramirezae, whereas the latter ate more Coleoptera and Hemiptera (Heteroptera). With respect to Formicidae, female L. quilmes ate significantly more ants of three species characterized by soft bodies and lack of functional stings than males. These dietary differences between the two species and between males and females of L. quilmes suggest that, with similar prey availability, the lizards use resources differently. Further studies are needed to address these differences. Finally, we compare our results to those obtained in other Liolaemus species. Key words: diet, Liolaemus quilmes, Liolaemus ramirezae, syntopic species.